Law of Foreigners citizenship and Passports in India - Gurbax Singh (Delhi, 2003)
Keeping in the mind the need to put together the whole gamut of legislative enactments and rules in this area under a single cover, the work not only brings to the reader a comprehensive compilation of statues but also seeks to clarify the doubts through authoritative comments by the author. Divided in six parts, and with every part taking care of a specific area of law realating to Foreigners, Baggage, Foreign Exchange, Citizenship, Passports together with realted provisions, the book goes on to deal with the subject comprehensively to the last detail. The work is of importance and would prove extremely useful to the judges, lawyers, research scholars and to all others who are concerned with this area of law.
Keywords: Foreigners-Laws